Omphalomesenteric duct remnant in a child with neurofibromatosis type 1. - Morrison, E.; Forsyth, L.; Ngan, K. (European Journal of Pediatric Dermatology, 2025)
Omphalomesenteric duct remnants occur due to incomplete resorption of the embryologic connection between the yolk sac and the primitive midgut during gestation. We present the case of a 6-year-old boy with a family history of neurofibromatosis type 1 presenting with café au lait macules and an umbilical nodule, histology of which confirmed an omphalomesenteric duct remnant. There is no known association between neurofibromatosis type 1 and omphalomesenteric duct remnants, but investigation and management of these lesions is discussed.